The Impact of Cultural Differences on Business Communication Between Vietnam and China - Bich Dang, Phuong; Xiao Yun, Huang (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
Since the 21st century, Vietnamese business activities have continuously developed and expanded, especially with the increasingly close trade relationship with China. In the context of the international market, business communication between Vietnam and China is not only an interaction between enterprises of the two countries but also involves cultural exchanges between countries. There are many cultural differences in business communication between Vietnam and China, which greatly impact international business activities. For Vietnam, which is integrating with the world economy, long-term cooperation with Chinese enterprises is crucial, and therefore, further strengthening a deep understanding of Chinese culture is also essential. With the continuous promotion of business relations between Vietnam and China, Vietnamese businessmen are deeply influenced by Chinese business culture and the Chinese economy, and economic globalization is increasingly deeply rooted in people's hearts. However, there are still some cultural differences in business communication activities between Vietnam and China, resulting in inevitable obstacles in business communication. The state and enterprises should take these obstacles seriously on time, and optimization plans for short-term and long-term promotion of business activities should be continuously proposed to reduce and eliminate these hidden dangers and strengthen individual and collective processing capabilities. Resolving cultural differences will improve the effectiveness of business communication between Vietnam and China, promote friendly economic development between the two countries, and enable Vietnamese businesses to maintain a stable economic position in world trade activities and seek strength.